2002
DOI: 10.2114/jpa.21.159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laughing and Weeping on Mood and Heart Rate Variability.

Abstract: We investigated the effects of laughing and weeping induced by watching comedy and tragedy videos on mood and autonomic nervous function. Ten healthy female subjects volunteered for the experiment. Chest electrocardiogram and respiration curve were recorded before, after, and during watching a comedy or a tragedy video. We also asked them to fill out profiles of mood states (POMS) to evaluate their mood states while watching videos. Autonomic nervous function was estimated by spectral analysis of heart rate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 28 publications
(20 reference statements)
4
43
1
3
Order By: Relevance
“…19 Moderate or strong exercise activates sympathetic activity with simultaneous withdrawal of parasympathetic nerve activity. 20,21 It has been shown that laughter has strong but transient effects on the autonomic nervous system 22 and may contribute to cardioprotection in some personality traits. 10 In some studies, laughter affected hormonal response, mostly as an effect of increased level of circulating catecholamines.…”
Section: Energy Expenditure Of Laughter Ms Buchowski Et Almentioning
confidence: 99%
“…19 Moderate or strong exercise activates sympathetic activity with simultaneous withdrawal of parasympathetic nerve activity. 20,21 It has been shown that laughter has strong but transient effects on the autonomic nervous system 22 and may contribute to cardioprotection in some personality traits. 10 In some studies, laughter affected hormonal response, mostly as an effect of increased level of circulating catecholamines.…”
Section: Energy Expenditure Of Laughter Ms Buchowski Et Almentioning
confidence: 99%
“…Interestingly, power spectrum analysis has revealed that certain emotions (e.g., anger, appreciation) can be differentiated by comparing different parts of the power spectrum captured while experiencing those emotions [27]. A similar approach has also been used to understand heart rate changes over an extended period of time-50 minutes-while participants watched comedies or tragedies [37].…”
Section: Theory-based Expectationsmentioning
confidence: 99%
“…'n Toename in die LF/HF-verhouding en 'n verlaging in die som van die totale drywing in die LF-en HF-gebiede word geassosieer met verlaagde HTV. 5,11 'n Drywingspektrumanalise van normale HTV en verlaagde HTV is uitgebeeld in figuur 1A …”
Section: Tyddomeinanaliseunclassified
“…Korrekte interpretasie van harttempovariasiedata open nie net 'n venster op die komplekse dinamiek van outonome harttemporegulering tydens die handhawing van homeostase nie, maar verleen ook insig in die oorhoofse funksionering van die outonome senuweestelsel. 5,6 Dit is algemeen bekend dat outonome kardiovaskulêre beheer 'n bepalende rol speel in fatale kardiale insidente. Verlaagde HTV is 'n bekende indikator van abnormale outonome beheer van die hart met gepaardgaande verhoogde risiko vir spontane ventrikulêre aritmias wat 'n teken is van elektriese onstabiliteit van die miokardium.…”
unclassified